Sensors for temperature measurement : error measurement of type K thermocouple - Maulana, Bin Hanapi. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Thermocouple is a type of sensors to measure temperature. It is based on the principle that when two dissimilar metals are joined, a predictable voltage will be generated in accordance to the difference in temperature between the measuring junction and the reference junction. This project is about the type K thermocouple used in Temperature Measurement equipment that is available at UNIMAS' Mechanical Engineering laboratory. The equipment is named THI. The main objective of this project is to determine the error range occurs in type K thermocouple used in THI. The error range will consist of error range based on experimental and linearized results. These errors will then to be compared to the manufacturer's specification.